Pancreatic Ductal Bicarbonate Secretion: Challenge of the Acinar Acid Load - Hegyi, Peter; Maléth, Jozsef; Venglovecz, Viktória; Rakonczay, Zoltan (Frontiers in Physiology, 2011)
Acinar and ductal cells of the exocrine pancreas form a close functional unit. Although most studies contain data either on acinar or ductal cells, an increasing number of evidence highlights the importance of the pancreatic acinar-ductal functional unit. One of the best examples for this functional unit is the regulation of luminal pH by both cell types. Protons co-released during exocytosis from acini cause significant acidosis, whereas, bicarbonate secreted by ductal cells cause alkalization in the lumen. This suggests that the first and probably one of the most important role of bicarbonate secretion by pancreatic ductal cells is not only to neutralize the acid chyme entering into the duodenum from the stomach, but to neutralize acidic content secreted by acinar cells. To accomplish this role, it is more than likely that ductal cells have physiological sensing mechanisms which would allow them to regulate luminal pH. To date, four different classes of acid-sensing ion channels have been identified in the gastrointestinal tract (transient receptor potential ion channels, two-pore domain potassium channel, ionotropic purinoceptor and acid-sensing ion channel), however, none of these have been studied in pancreatic ductal cells. In this mini-review, we summarize our current knowledge of these channels and urge scientists to characterize ductal acid-sensing mechanisms and also to investigate the challenge of the acinar acid load on ductal cells.